Improving crop productivity in sustainable agriculture (Wiley-Blackwell, 2013)
mproving Crop Productivity in Sustainable Agriculture includes an excellent mix of specific examples, such as the creation of nutritionally-fortified rice and a discussion of the political and economic implications of genetically engineered food.